Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Evaluate the series $$\sum_{k=0}^{\infty}\frac{1}{(4k+1)(4k+2)(4k+3)(4k+4)}=?$$

Can you help me ? This is a past contest problem.

share|improve this question
7  
You could try breaking it into partial fractions. –  Jair Taylor Oct 30 '12 at 5:01
    
@JairTaylor: Or using by the Beta function, which gives a continuous analogue to partial fractions. –  Eric Naslund Oct 30 '12 at 5:05
    
@Jair Taylor:Yes! in fact i know the results of this problem. I want to know some different method. Thank you very much. –  Dao yi Peng Oct 30 '12 at 5:06
    
@EricNaslund:Thank you! I and you use the same method. I have used Gamma fuuction. –  Dao yi Peng Oct 30 '12 at 5:12
2  
Dao: Since you know the results, why not mention it (and where you read them)? –  Did Oct 30 '12 at 7:14

4 Answers 4

up vote 15 down vote accepted

This is Problem 2 of Day 1 of the 2010 International Mathematics Competition. If you go to the competition website, you can find several solutions, but here is a solution I came up with using the Beta function:

We have the identity ** $$\frac{3!}{(4l+1)(4l+2)(4l+3)(4l+4)}=\int_{0}^{1}x^{4l}(1-x)^{3}\text{d}x.$$ Thus we may write $$\sum_{l=0}^{\infty}\frac{1}{(4l+1)(4l+2)(4l+3)(4l+4)}=\sum_{l=0}^{\infty}\frac{1}{3!}\int_{0}^{1}x^{4l}(1-x)^{3}\text{d}x.$$ Rearranging the order of summation and integration yields $$\frac{1}{6}\int_{0}^{1}\left(\sum_{l=0}^{\infty}x^{4l}\right)(1-x)^{3}\text{d}x=\frac{1}{6}\int_{0}^{1}\frac{(1-x)^{3}}{1-x^{4}}\text{d}x=\frac{1}{6}\int_{0}^{1}\frac{(1-x)^{2}}{(1+x)(1+x^{2})}\text{d}x.$$ Using partial fractions to split up the integrand we then have $$\frac{1}{6}\int_{0}^{1}\frac{2}{1+x}-\frac{1+x}{1+x^{2}}\text{d}x=\frac{1}{3}\int_{0}^{1}\frac{1}{1+x}-\frac{1}{6}\int_{0}^{1}\frac{1}{1+x^{2}}\text{d}x-\frac{1}{6}\int_{0}^{1}\frac{x}{1+x^{2}}\text{d}x$$ and evaluating the integrals yields $$=\frac{1}{3}\log2-\frac{1}{6}\frac{\pi}{4}-\frac{1}{12}\log2=\frac{1}{4}\log2-\frac{\pi}{24}$$

** This identity follows from the fact that $\text{B}(x,y)=\frac{\Gamma(x)\Gamma(y)}{\Gamma(x+y)}$ where $\text{B}(x,y)$ is the Beta Function, but it also follows directly from expanding and integrating since $l$ is an integer. Essentially, this integral encodes the partial fraction decomposition.

share|improve this answer
    
Where did the 3! come from? –  Jair Taylor Oct 30 '12 at 5:21
    
@JairTaylor: It is a $\Gamma(4)$ because there are $4$ terms. –  Eric Naslund Oct 30 '12 at 6:26
1  
Sledgehammers get the job done, too! :-) –  robjohn Oct 31 '12 at 19:03

Let \begin{align}S_n & =\sum_{k=0}^{n}\frac{1}{(4k+1)(4k+2)(4k+3)(4k+4)}\\ & =\sum_{k=0}^{n}\left(\frac{1}{6}\frac{1}{4k+1}-\frac{1}{2}\frac{1}{4k+2}+\frac{1}{2}\frac{1}{4k+3}-\frac{1}{6}\frac{1}{4k+4}\right). \end{align} $$A_n=\sum_{k=0}^{n}\left(\frac{1}{4k+1}-\frac{1}{4k+3}\right),$$ $$B_n=\sum_{k=0}^{n}\left(\frac{1}{4k+1}-\frac{1}{4k+2}+\frac{1}{4k+3}-\frac{1}{4k+4}\right),$$ and $$C_n=\sum_{k=0}^{n}\left(\frac{1}{4k+2}-\frac{1}{4k+4}\right).$$ It is easy check that $$S_n=\frac{1}{3}B_n-\frac{1}{6}A_n-\frac{1}{6}C_n.$$ Therefore, $$\lim_{n\to\infty}S_n=\lim_{n\to\infty}\frac{2B_n-A_n-C_n}{6}=\frac{2\ln 2-\dfrac{\pi}{4}-\dfrac{1}{2}\ln 2}{6}=\frac{1}{4}\ln 2-\frac{\pi}{24}.$$

share|improve this answer
    
-1: This is an incorrect way though you end up getting the right answer. You cannot rearrange terms since after splitting it as partial fractions the sum diverges absolutely. –  user17762 Oct 30 '12 at 15:51
    
This is the same reason why the method in my edit section ends up giving an incorrect answer. –  user17762 Oct 30 '12 at 15:52
    
@Marvis: The decomposition Dao Yi Peng did can be justified, but undoubtedly he needs to say more than "It is easy to check that"... DaoYiPeng: In general if it is so easy, it should take less than half a sentence to explain why. If it takes more than that, then you should probably explain it anyway. –  Eric Naslund Oct 30 '12 at 17:52
    
@EricNaslund True. He needs to argue out why the decomposition can be done in the first place. And actually I am interested in the justification since those series are not absolutely convergent. How/Why does his rearrangement give the right answer? –  user17762 Oct 30 '12 at 17:53
1  
There is still something wrong here. $A_n\to\frac\pi4$, $B_n\to\log(2)$, and $C_n\to\frac12\log(2)$. So as computed above, $S_n\to\frac\pi{12}-\frac14\log(2)$. I think that $S_n=\frac13B_n-\frac16A_n-\frac16C_n$ is correct –  robjohn Oct 31 '12 at 19:37

\begin{align} f(k) & = \dfrac1{(4k+1)(4k+2)(4k+3)(4k+4)}\\ & = - \dfrac12 \dfrac1{4k+2} + \dfrac16 \dfrac1{4k+1} + \dfrac12 \dfrac1{4k+3} - \dfrac1{6} \dfrac1{4k+4} \end{align} $$f(k) = -\dfrac12 \int_0^1 t^{4k+1} dt + \dfrac16 \int_0^1 t^{4k} dt + \dfrac1{2} \int_0^1 t^{4k+2} dt - \dfrac1{6} \int_0^1 t^{4k+3} dt $$ $$S = \sum_{k=0}^{\infty} f(k) = \sum_{k=0}^{\infty} \left(-\dfrac12 \int_0^1 t^{4k+1} dt + \dfrac16 \int_0^1 t^{4k} dt + \dfrac1{2} \int_0^1 t^{4k+2} dt - \dfrac1{6} \int_0^1 t^{4k+3} dt \right)$$ $$\sum_{k=0}^{\infty} t^{4k+1} = \dfrac{t}{1-t^4}$$ $$\sum_{k=0}^{\infty} t^{4k} = \dfrac1{1-t^4}$$ $$\sum_{k=0}^{\infty} t^{4k+2} = \dfrac{t^2}{1-t^4}$$ $$\sum_{k=0}^{\infty} t^{4k+3} = \dfrac{t^3}{1-t^4}$$ $$S = \int_0^1 \left(-\dfrac12 \dfrac{t}{1-t^4} + \dfrac16 \dfrac1{1-t^4} + \dfrac12 \dfrac{t^2}{1-t^4} - \dfrac1{6} \dfrac{t^3}{1-t^4} \right) dt$$ $$g(t) = -\dfrac12 \dfrac{t}{1-t^4} + \dfrac16 \dfrac1{1-t^4} + \dfrac12 \dfrac{t^2}{1-t^4} - \dfrac1{6} \dfrac{t^3}{1-t^4}$$ $$6g(t) = \dfrac{1-3t+3t^2 - t^3}{(1-t^4)} = \dfrac{(1-t)^3}{1-t^4} = \dfrac{1-2t+t^2}{(1+t)(1+t^2)}$$ $$6g(t) = \dfrac2{t+1} - \dfrac1{1+t^2} - \dfrac{t}{1+t^2}$$ $$\int_0^1 6 g(t) dt = \int_0^1 \dfrac{2 dt}{1+t} - \int_0^1 \dfrac1{1+t^2} - \int_0^1 \dfrac{t}{1+t^2} = 2 \log(2) - \dfrac{\pi}4 - \dfrac12 \log(2) = \dfrac32 \log(2) - \dfrac{\pi}4$$ Hence, $$S = \int_0^1 g(t) dt = \dfrac14 \log(2) - \dfrac{\pi}{24}$$

EDIT

For what it is worth, in the first step if we write \begin{align} f(k) & = \dfrac1{(4k+1)(4k+2)(4k+3)(4k+4)}\\ & = - \dfrac14 \dfrac1{2k+1} + \dfrac16 \dfrac1{4k+1} + \dfrac12 \dfrac1{4k+3} - \dfrac1{24} \dfrac1{k+1}\\ & = -\dfrac14 \int_0^1 t^{2k} dt + \dfrac16 \int_0^1 t^{4k} dt + \dfrac1{2} \int_0^1 t^{4k+2} dt - \dfrac1{24} \int_0^1 t^k dt \end{align} not surprising you get an incorrect answer.

$$f(k) = -\dfrac14 \int_0^1 t^{2k} dt + \dfrac16 \int_0^1 t^{4k} dt + \dfrac1{2} \int_0^1 t^{4k+2} dt - \dfrac1{24} \int_0^1 t^k dt $$ $$S = \sum_{k=0}^{\infty} f(k) = \sum_{k=0}^{\infty} \left(-\dfrac14 \int_0^1 t^{2k} dt + \dfrac16 \int_0^1 t^{4k} dt + \dfrac1{2} \int_0^1 t^{4k+2} dt - \dfrac1{24} \int_0^1 t^k dt \right)$$ $$\sum_{k=0}^{\infty} t^{2k} = \dfrac1{1-t^2}$$ $$\sum_{k=0}^{\infty} t^{4k} = \dfrac1{1-t^4}$$ $$\sum_{k=0}^{\infty} t^{4k+2} = \dfrac{t^2}{1-t^2}$$ $$\sum_{k=0}^{\infty} t^{k} = \dfrac1{1-t}$$ $$S = \int_0^1 \left(-\dfrac14 \dfrac1{1-t^2} + \dfrac16 \dfrac1{1-t^4} + \dfrac12 \dfrac{t^2}{1-t^4} - \dfrac1{24} \dfrac1{1-t} \right) dt = \int_0^1 g(t) dt$$ $$g(t) = -\dfrac14 \dfrac1{1-t^2} + \dfrac16 \dfrac1{1-t^4} + \dfrac12 \dfrac{t^2}{1-t^4} - \dfrac1{24} \dfrac1{1-t}$$ $$g(t) = -\dfrac14 \dfrac1{1-t^2} + \dfrac16 \dfrac{3t^2+1}{1-t^4} - \dfrac1{24} \dfrac1{1-t} = -\dfrac1{24} \dfrac{t+7}{1-t^2} + \dfrac16 \dfrac{3t^2+1}{1-t^4}$$ $$g(t) = \dfrac1{24} \dfrac{12t^2+4 - (1+t^2)(7+t)}{1-t^4} = \dfrac1{24} \dfrac{-3-t+5t^2-t^3}{1-t^4} = \dfrac1{24} \dfrac{(1-t)(t^2-4t-3)}{1-t^4}$$ $$24 g(t) = \dfrac{t^2 - 4t-3}{(1+t)(1+t^2)} = \dfrac{t^2 +1 - 4t-4}{(1+t)(1+t^2)} = \dfrac{t^2+1}{(1+t)(1+t^2)} - 4 \dfrac{(1+t)}{(1+t)(1+t^2)}$$ $$24g(t) = \dfrac1{1+t} - \dfrac4{1+t^2}$$ Hence, $$S = \int_0^1 g(t) dt = \dfrac1{24} \left(\int_0^1 \dfrac{dt}{1+t} -4 \int_0^1 \dfrac{dt}{1+t^2}\right) = \dfrac1{24} \left( \left. \log(1+t) \right \vert_{t=0}^{t=1} - 4 \left. \arctan(t) \right \vert_{t=0}^{t=1}\right)$$ $$S = \dfrac1{24} \left( \log(2) - 4 \dfrac{\pi}4\right)$$

share|improve this answer

Start with the Mercator series $$ \sum_{k=0}^\infty\frac{(-1)^k}{k+1}=\log(2) $$ and Gregory's series $$ \sum_{k=0}^\infty\frac{(-1)^k}{2k+1}=\frac\pi4 $$ The Heaviside Method yields $$ \begin{align} &\frac6{(4k+1)(4k+2)(4k+3)(4k+4)}\\ &=\frac1{4k+1}-\frac3{4k+2}+\frac3{4k+3}-\frac1{4k+4}\\ &=\color{#C00000}{\left(\frac2{4k+1}-\frac2{4k+2}+\frac2{4k+3}-\frac2{4k+4}\right)}\\ &-\,\color{#00A000}{\left(\frac1{4k+1}-\frac1{4k+3}\right)}-\color{#0000FF}{\left(\frac1{4k+2}-\frac1{4k+4}\right)} \end{align} $$ Note that the parts in red, green, and blue are all $O\left(\frac1{k^2}\right)$, so their sums converge absolutely.

Thus, $$ \begin{align} \sum_{k=0}^\infty\frac6{(4k+1)(4k+2)(4k+3)(4k+4)} &=\color{#C00000}{2\log(2)}-\color{#00A000}{\frac\pi4}-\color{#0000FF}{\frac12\log(2)}\\ &=\frac32\log(2)-\frac\pi4 \end{align} $$ Dividing by $6$ yields $$ \sum_{k=0}^\infty\frac1{(4k+1)(4k+2)(4k+3)(4k+4)}=\frac14\log(2)-\frac\pi{24} $$

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.